2016
DOI: 10.1039/c5cs00777a
|View full text |Cite
|
Sign up to set email alerts
|

Multi-functional electrospun nanofibres for advances in tissue regeneration, energy conversion & storage, and water treatment

Abstract: Tissue regeneration, energy conversion & storage, and water treatment are some of the most critical challenges facing humanity in the 21st century. In order to address such challenges, one-dimensional (1D) materials are projected to play a key role in developing emerging solutions for the increasingly complex problems. Eletrospinning technology has been demonstrated to be a simple, versatile, and cost-effective method in fabricating a rich variety of materials with 1D nanostructures. These include polymers, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
138
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 331 publications
(139 citation statements)
references
References 50 publications
0
138
0
1
Order By: Relevance
“…Electrospinning is a facile and cheap method to fabricate various size of NWs on a large scale, which has been widely utilized for tissue regeneration, energy conversion and storage, and water treatment, etc 30, 31. Furthermore, through simple modification, electrospinning can achieve highly ordered nanowire arrays (NWA) on various substrates as well 32.…”
Section: Introductionmentioning
confidence: 99%
“…Electrospinning is a facile and cheap method to fabricate various size of NWs on a large scale, which has been widely utilized for tissue regeneration, energy conversion and storage, and water treatment, etc 30, 31. Furthermore, through simple modification, electrospinning can achieve highly ordered nanowire arrays (NWA) on various substrates as well 32.…”
Section: Introductionmentioning
confidence: 99%
“…[34,35] Recent works have demonstrated that electrospinning is becoming a versatile, simple, cost-effective, and scalable strategy for producing 1D nanostructures, which possess many outstanding properties, including good mechanical strength, excellent flexibility, superior electrical conductivity, and large surface area to volume ratios. [37][38][39][40][41] Nevertheless, a relatively high carbon content resulting from the carbonization of as-electrospun polymers and lack of sufficient porosity could block the diffusion paths of the electrolytes and ions during charge/discharge processes, leading to decreased power and energy. [6,42] Moreover, particles of TMOs tend to grow and aggregate during carbonization of polymeric nanofibers and are usually located on the surfaces of the nanofibers, which is potentially harmful to the formation of a stable solid electrolyte interphase (SEI) layer and results in unsatisfactory electrochemical performance.…”
Section: Introductionmentioning
confidence: 99%
“…[26][27][28] Nanobiomaterials have been considered better candidates than the traditional tissue engineering scaffolds because these nanoscale biomaterials can effectively mimic the characters of natural tissues, in which cells directly contact their surrounding nanoscale ECM, which exerts a key role in supplying mechanical support, directing cell adhesion and growth, as well as regulating tissue development, homeostasis, and regeneration. 29,30 In the interest of simulating more chemical and biological components of the natural ECM, various electrospun nanoscale scaffolds have been fabricated to imitate the topography of natural ECM for tissue engineering and regenerative medicine.…”
Section: Discussionmentioning
confidence: 99%